Feasibility of LTE 700 MHz Digital Dividend for Broadband Development Acceleration in Rural Areas - Denny Setiawan; Djamhari Sirat; Dadang Gunawan (Journal of ICT Research and Applications, 2012)
The need of broadband services to reduce digital divide in rural areas had increased in the recent years. The government of the Republic Indonesia shared similar intention and had set guidance of ICT development in its "economic master plan" and "medium term development plan". This paper addressed feasibility and suitability of its implementation in Indonesia, by conducting assessment of possible solutions. Using mixed method, the study was started with qualitative approach to identify possible options, conducted benchmarking and case study analysis to narrow down the options and finally conducted quantitative calculation for the two remaining options and measure performance of the solutions. The results of analysis concluded that early implementation of LTE in 700 MHz Digital Dividend would be feasible in certain geographical areas to fasten the broadband plan development in Indonesia.